Peran Quad (AS, India, Jepang, Australia) dalam Stabilitas Indo-Pasifik: Perspektif dari Konflik Laut China Selatan - Tarsito, Tarsito; Riyanta, Stanislaus; Daryanto, Eko (Syntax Literate, 2025)
The Indo-Pacific region has become the center of global geopolitical attention, especially in the South China Sea, which is rich in natural resources and is a strategic trade route for many countries. The conflict in the South China Sea is fueled by overlapping claims from various countries, including China, Vietnam, the Philippines, Malaysia and Brunei, which have the potential to provoke military tensions. The Quad, which consists of the United States, India, Japan, and Australia, has emerged as an important actor in maintaining stability in the region by conducting security cooperation, joint military exercises, and maritime patrols. Although not a formal military alliance, the Quad serves as a strategic counterweight to China's influence in the Indo-Pacific. This paper explores how the Quad is facing geopolitical challenges, including differences of interest among members and China's reaction, as well as discussing the alliance's potential in promoting regional stability through multilateral approaches. In addition to the military aspect, the Quad also focuses on infrastructure development and economic diplomacy as a step towards creating a free, open and stable Indo-Pacific.